AB0672 Assessment of Hands and Mouth Disability in Systemic Sclerosis Patients. (9th June 2015) - Molina, M.J.; Nitsche, A.; Gervilla, A.L.; Sansinanea, P.; Sarano, J.; Amitrano, C.; Pucci, P.; Mamani, M.; Oliver, M.; Scarafia, S.; Asnal, C.A.; Gallardo, M.
Abstract : Background: Skin involvement, sclerodactylia, tendon and joint damage, digital ulcers (DU) and flexion contracture of hand fingers (FCHF) are frequent in systemic sclerosis (SSc) patients leading to disability of the hands. Skin face affectation produces mouth and facial physiognomy alterations. Several scales evaluate hand and mouth disability in SSc, such as Cochin Hand Function Scale (CHFS), Modified Kapandji Index (MKI) and Mouth Handicap In Systemic Sclerosis (MHISS) but there are not assessed in daily clinical practice. Objectives: 1-To evaluate hand disability using CHFS and MKI. 2-To determine mouth handicap using MHISS in SSc patients. Methods: Transversal and multicenter study with 74 SSc patients (1980 ACR criteria) from Argentina. We determine age, gender, age at diagnosis, evolution time, SSc forms: diffuse (dSSc) and limited (lSSc), presence of DU, FCHF, complete or incomplete fist, digital amputation (DA: spontaneously or by surgery), and bone resorption of hand distal phalanxes (BRDP). Hand disability was evaluated by CHFS: 18 questions of daily life activities and hand mobility using MKI: 3 subsets: 1-thumb opposition, 2- flexion of four long fingers and 3- extension of four long fingers. We evaluated mouth disability using MHISS: 12 questions of mouth daily activities and facial physiognomy. Statistical analysis: frequencies, chi-square test, Fisher exact test, T-test, Mann-Whitney test and lineal correlation coefficient. P value of <0.05 was considered significant. Results: 87.8% were women. Age patients was 53.6±13.4 years, 47.0±14.3 years at diagnosis and evolution time of 86, 1±79.6 months. dSSc was observed in 60.8% of patients. SSc patients had sclerodactylia in 79.7% and DU in 21.6%: 13.5% in dSSc and 8.1% in lSSc. Three patients presented DA, 2 spontaneously and 1 by surgery. FCHF and BRDP were present in 28.4% and in 10.8% of patients, respectively. Patients completed fist in 35.1%. Mean CHFS was of 22.7±22.7, mean MKI of 78.6±26.1 and mean MHISS of 21.9±12. Female had significantly less age, less age at diagnosis and higher MHISS score. We did not found significant association between SSc forms and DU or FCHF. Sclerodactylia was associated with higher age (p=0.03), higher evolution time (p=0.03), higher FCHF frequency (p=0.004), higher incomplete fist (p=0.001), higher CHFS score (p=0.007), less MKI score (p=0.0001) and higher MHISS score (p=0.002). Patients without DU had less FCHF (p=0.0001), less BRDP (p=0.001) and higher complete fist (p=0.0001). Patients with DU, FCHF, incomplete fist and BRDP had significantly higher CHFS score, less MKI score and higher MHISS score. Conclusions: 1- To our knowledge these is the largest SSc cohort patients evaluating disability index in Argentina. 2- Women had higher involvement of mouth and facial physiognomy alterations. 3- SSc patients with sclerodactylia, DU, FCHF, incomplete fist and BRDP presented higher hand and mouth disability. References: Arthritis Rheum 2007;57:94-102. Ann Rheum Dis 2007;66:1651-1655. Disclosure of Interest: None declared